Analisis Kebijakan Demokratisasi sebagai Instrumen Kekuasaan dalam Politik Luar Negeri Amerika Serikat - Hamado, Kardina; Sikky, Rahmat (Journal of Integrative International Relations, 2022)
Democratization is US policy which campaign democrazy as the norms and values through realist and liberal strategy in foreign politic. This research is aimed to know the interest behind the democratization policy and US authority position globally. This reasearch used national interests concept, foreign policy and foreign politic by applying descriptive analysis method. The result of this research showed that nations thus considered to have violated the democrazy principles are a thread to washington intererst occurrence. Democratization as instrument is proven beneficially to US to intervence by economic and military politic to determine democracy standard which affected toward US impact and authority in various country significantly.